2017
DOI: 10.1186/s13073-017-0433-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic diagnosis for children with intellectual disability and/or developmental delay

Abstract: BackgroundDevelopmental disabilities have diverse genetic causes that must be identified to facilitate precise diagnoses. We describe genomic data from 371 affected individuals, 309 of which were sequenced as proband-parent trios.MethodsWhole-exome sequences (WES) were generated for 365 individuals (127 affected) and whole-genome sequences (WGS) were generated for 612 individuals (244 affected).ResultsPathogenic or likely pathogenic variants were found in 100 individuals (27%), with variants of uncertain signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
192
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(202 citation statements)
references
References 43 publications
8
192
0
2
Order By: Relevance
“…None of the variants in this table were returned to probands at time of the first analysis, nor was ACMG scoring or criteria explicitly used at that time. ‡ Note that this variant was previously reported with our initial study findings 8 , although the variant was recently found in one additional unrelated proband in our study, represented here. § ACMG scoring criteria do not apply to UPD. …”
Section: Tablesupporting
confidence: 54%
See 1 more Smart Citation
“…None of the variants in this table were returned to probands at time of the first analysis, nor was ACMG scoring or criteria explicitly used at that time. ‡ Note that this variant was previously reported with our initial study findings 8 , although the variant was recently found in one additional unrelated proband in our study, represented here. § ACMG scoring criteria do not apply to UPD. …”
Section: Tablesupporting
confidence: 54%
“…An initial reanalysis effort was described in an analysis of the first 371 affected probands 8 , but an expanded and improved reanalysis pipeline, including new findings, approaches, and implications, is presented here.…”
Section: Introductionmentioning
confidence: 99%
“…NBEA variants were identified in 22 previously unreported cases and two cases already reported in the literature 7 . All variants were confirmed to be de novo with the exception of individual 13.…”
Section: Resultsmentioning
confidence: 95%
“…It is not currently associated with disease in the Online Mendelian Inheritance in Man (OMIM) database but is a candidate gene for autism based on linkage studies and the identification of microdeletions and a reciprocal balanced translocation involving NBEA in patients with autism 26 . More recently, two de novo NBEA variants were identified through whole exome sequencing (WES) in large cohorts of patients with neurodevelopmental disease (NDD) phenotypes, implicating NBEA as a candidate gene 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the relevant clinical information, details about each variant, inheritance, number of genes tested, ACMG classification, and Online Mendelian Inheritance in Man disease entities related to specific genes. [19][20][21][22][23][24] The complete panel results for each patient, including genetic variants considered out of the scope of the present study, are available as Appendix S2.…”
Section: Resultsmentioning
confidence: 99%